Public support for European cooperation in the procurement, stockpiling and distribution of medicines. (17th January 2021) - Beetsma, Roel; Burgoon, Brian; Nicoli, Francesco; de Ruijter, Anniek; Vandenbroucke, Frank
Abstract: Background: The COVID-19 outbreak has heightened ongoing political debate about the international joint procurement of medicines and medical countermeasures. The European Union (EU) has developed what remains largely contractual and decentralized international procurement cooperation. The corona crisis has broadened and deepened public debate on such cooperation, in particular on the scope of cooperation, solidarity in the allocation of such cooperation, and delegation of cooperative decision-making. Crucial to political debate about these issues are public attitudes that constrain and undergird international cooperation. Methods: Our survey includes a randomized survey experiment (conjoint analysis) on a representative sample in five European countries in March 2020, informed by legal and policy debate on medical cooperation. Respondents choose and rate policy packages containing randomized mixes of policy attributes with respect to the scope of medicines covered, the solidarity in conferring priority access and the level of delegation. Results: In all country populations surveyed, the experiment reveals considerable popular support for European cooperation. Significant majorities preferred cooperation packages with greater rather than less scope of medicines regulated; with priority given to most in-need countries; and with delegation to EU-level rather than national expertise. Conclusion: Joint procurement raises delicate questions with regard to its scope, the inclusion of cross-border solidarity and the delegation of decision-making, that explain reluctance toward joint procurement among political decision-makers. This research shows that there is considerable public support across different countries in favor of centralization, i.e. a large scope and solidarity in the allocation and delegation of decision-making.